Don’t go all “TED Talks” on them, but... make a good presentation! – teaching the oral genre through the didactic sequence procedures - Timmermann, Rafael de Souza; Sturm, Luciane (Revista da ABRALIN, 2021)
Language teaching in a higher education (HE) environment is complex and challenging, much more so when we consider the contemporary demands concerning the additional languages, specifically, English. We start from the understanding that a genre-based approach in teaching is established as a positive strategy for teaching/learning and developing students’ linguistics skills. However, reflections and questions emerge when, as professors, we discuss the role of the HE and its disciplines in potentializing students' actions through language in real social practices, which can contribute to their personal and professional development. Our premise, as well as a problem, considering there seems to be a gap regarding this point, is that academic oral genres should be taught in a systematic and clear way in HE. Seeking to solve this problem, by the supports of Applied Linguistics, we structured two questions to guide this qualitative and exploratory study: 1) What would be an appropriate theory-oriented approach to support the teaching of oral genres in HE? 2) Considering the HE contexts, what would an achievable proposal aiming at the mastery of an oral genre be like? In order to answer these questions, we brought a theoretical discussion and also a Didactic Sequence (DS) regarding oral presentations in academic events as a proposal to show that the Socio-discursive Interactionism and the DS model can be powerful educators’ allies in planning and organizing classes that allow students to perform through language in different academic routines